2016
DOI: 10.1007/s12020-016-1095-2
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and determinants of hypothyroidism in hospitalized patients with type 2 diabetes mellitus

Abstract: The purpose of this study was to investigate the prevalence of hypothyroidism among hospitalized patients with type 2 diabetes mellitus and its related factors, and to assess the prevalence of macrovascular and microvascular diseases among type 2 diabetes mellitus inpatients with hypothyroidism and euthyroidism. A total of 1662 type 2 diabetes mellitus inpatients hospitalized at the Metabolic Diseases Hospital, Tianjin Medical University from 1 January 2008 to 1 March 2013 were included in this study. Informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…This wide range could reflect differences in age, gender and iodine intake in the populations surveyed. Female gender, older age, obesity, TPO-Ab positivity and hospitalization are associated with an increased risk of developing hypothyroidism in T2D (98,(100)(101)(102)(103). A significant increased risk of hypothyroidism was observed in patients with T2D over 65 years of age with an odds ratio (OR) of 4.2 and a clear difference between males and females (OR 4.82 vs. 2.60), obese and non-obese patients (OR 2.56 vs. 3.11), and presence or absence of thyroid auto-antibodies (OR 4.26 vs. 2.93) (101).…”
Section: Prevalence Of Hypothyroidism In T2dmentioning
confidence: 99%
See 1 more Smart Citation
“…This wide range could reflect differences in age, gender and iodine intake in the populations surveyed. Female gender, older age, obesity, TPO-Ab positivity and hospitalization are associated with an increased risk of developing hypothyroidism in T2D (98,(100)(101)(102)(103). A significant increased risk of hypothyroidism was observed in patients with T2D over 65 years of age with an odds ratio (OR) of 4.2 and a clear difference between males and females (OR 4.82 vs. 2.60), obese and non-obese patients (OR 2.56 vs. 3.11), and presence or absence of thyroid auto-antibodies (OR 4.26 vs. 2.93) (101).…”
Section: Prevalence Of Hypothyroidism In T2dmentioning
confidence: 99%
“…A large longitudinal study from Australia in women with T2D reported that SHypo is a common finding in T2D (97). It was the prevalent form of thyroid hormone deficiency in diabetic females (104,105) and patients with positive TPO-Ab (97,(101)(102)(103). In line with these results, a meta-analysis on 36 articles confirmed a higher pooled prevalence of SHypo in patients with T2D when compared with healthy controls (1.93-fold increased risk; 95% CI: 1.66-2.24) (104).…”
Section: Prevalence Of Hypothyroidism In T2dmentioning
confidence: 99%
“…Subclinical hypothyroidism (SCH), characterized by elevated serum thyroid stimulating hormone (TSH) and normal serum free thyroxine (FT4) levels, is an independent risk factor for atherosclerosis, myocardial infarction, and non-alcoholic fatty liver disease (NAFLD) (14). Notably, emerging evidence shows that SCH and Type 2 diabetes mellitus (T2DM) are closely related and often occur together in individuals (5). We wondered whether SCH is also an independent risk factor for T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Type 1 diabetes mellitus and auto-immune thyroid disease are associated through common auto-immune links [5]. The underlying pathophysiological mechanisms of the repeatedly reported association between thyroid dysfunction and type 2 diabetes (T2DM) have not yet been fully elucidated [4, 6, 7]. Thyroid hormones have a large impact on glucose homeostasis [8], and both high and low thyroid hormone levels are associated with peripheral insulin resistance [911].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the association between thyroid dysfunction, in particular hypothyroidism, and T2DM [4, 6, 7], increasing plasma thyroid stimulating hormone (TSH) levels within the normal range are also associated with the prevalence of T2DM in a cross-sectional study in a general adult population in China [16]. Two longitudinal studies, from the Netherlands and Korea, show conflicting results [1719].…”
Section: Introductionmentioning
confidence: 99%